(untitled) (SCIÉNDO INGENIUM, 2026)
This research examines the application of the agile approach proposed by the Project Management Institute (PMI) in the management of innovation projects. The main objective was to determine whether this approach enables the validation of an innovation project. The study is applied in nature, with an explanatory design and a quantitative focus, utilizing statistical methods to analyze data collected from the population involved in the innovation project. The findings suggest that the implementation of the PMI’s agile approach may contribute to project validation by enhancing the acceptance of deliverables through continuous iterations. It is concluded that this approach shows potential effectiveness in validating innovation projects, supporting the alternative hypothesis and providing a foundation for both academic advancement and professional practice in project management. This study differs from previous research, which generally addresses the traditional PMI approach, by examining the application of the PMI agile framework in a context of sustainable innovation developed by a Peruvian microenterprise. This allows for demonstrating its relevance and adaptability in smaller-scale business environments with limited resources. This perspective adds value by analyzing how the PMI agile practices can contribute not only to project validation but also to strengthening sustainability and competitiveness in microenterprises.